Emerging technologies in educational institutions: assets and potential risks - François Victor Tochon (Universidad de Granada, 2012)
This article is a review of some aspects of research on electronic portfolios with a critical analysis of the pros and cons of the invasive use of new technologies for education. Besides the creation and conceptual composition of educative portfolios that help teachers grow professionnally, this instrument implies a formatting around artifacts posited as proofs of competence, which support an uncritical realist ontology that has its limitations. Thus networked learning and personal learning environments stimulate reflective teacher learning, but possibly lead portfolio users to confuse the indicator of performance with the actual competence. Portfolio creation takes much time on other activities that could be most beneficial (and could be complementary), such as shared reflection on personal belief systems. Universalist stands and standardisation seem to take the fore while educative humane value go back stage. The new wave of distance learning creates new risks in terms of depth and quality as well as health, related to the daily use of pulsed microwaves and radio frequencies. It is suggested that a mode of control independent from the financial milieux that capitalize on these innovations should be created.